Diabetes update workshop – ‘aligning innovation with tradition’ - Mohamed Shah, Fatimah Zaherah; Eddy Warman, Nur Aini; Awang, Mohd Hazriq; Mohamad, Aimi Fadilah; Abdul Ghani, Rohana (Faculty of Medicine, 2025)
The prevalence of Type 2 diabetes mellitus (DM) has been increasing exponentially in Malaysia, from 11.2% in 2011 to 18.3% in 2019 and to 15.6% in 2023. Additionally, the rate of undiagnosed diabetes is even more concerning, with almost 84% of adults in the younger age group of 18 to 29 years unaware of their diagnosis, according to the latest nationwide survey in 2023. The burden of morbidities due to diabetes complications highlights the Dr. Fatimah Zaherah Mohamed Shah, Dr. Nur Aini Eddy Warman, Dr. Mohd Hazriq Awang, Dr Aimi Fadilah Mohamad & Prof. Dr. Rohana Abdul Ghani PANEL discussion with robust participation from attendees. challenges in maintaining disease control. Advances in diabetes technologies have improved patient care, and many of these advances are becoming increasingly viable options in Malaysia. However, feasibility of use of these technologies in the general public will need enhanced practical knowledge among relevant healthcare workers. Hence, a diabetes management update workshop was designed for practical information dissemination among frontline medical practitioners from various training backgrounds on the use of modern technologies in DM management. This program was conducted at Hospital Al-Sultan Abdullah in February 2025, themed ‘Aligning Innovation with Tradition’.